Transparent and predictable labour conditions in European Union: Legal and comparative study - Victor Shcherbyna; Nataliya Rybak; Volodymyr Pikul; Oleh Vitruk; Yevheniia Kuprun (Unissula, 2023)
The article aims to evaluate the current innovations in Ukraine’s labor legislation for compliance with main legal acts that provide for transparent and predictable working conditions in the European Union. This article attempts to identify problems and shortcomings of the normative work of state bodies in this area and elaborate on the amendments to particular domestic legislative acts. The article analyzed the labor framework of the European Union and distinguished such shortcomings in the domestic legislation as the unclear definition of employee status, vague duration of probationary periods, undefined criteria for refusal and compensation for employees to refuse on-demand work, unresolved issue of minimum working hours, etc. The developed recommendations for amending legal acts of Ukraine make it possible to address the mentioned issues and receive timely and complete information about significant aspects of the work of Ukrainian employees.